NILAI-NILAI PEMBINAAN AKHLAK DALAM KEGIATAN EKSTRAKURIKULER DI MADRASAH ALIYAH MUSTAFAWIYAH PURBA BARU KABUPATEN MANDAILING NATAL - Herman Pelangi (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2017)
Islam  puts  moral  in  an  important  place  and  has  a  vital function  in  guiding  the  social  life  in  a  country.  Madrasah Aliyah   Mustafawiyah   Purba   Baru   Kabupaten   Mandailing Natal  has  a  strong  commitment  and  the  seriousness  in founding   the   extracurricular   education,   so   that   it   will produce   the   high   achievement,   the   interesting   point   of extracurricular education is it can give positive impact to the student’s moral.   The  formulations  of  the  problem  in  this  research  were  the extracurricular  activities,  the  founding  of  moral  value,  and the   endorser   and   inhibitor   factor   of   extracurricular   in founding  the  student’s  moral  in  Madrasah  Aliyah Mustafawiyah Purba Baru Kabupaten Mandailing Natal.   Moreover,   the   method   of   this   research   was   descriptive qualitatif  which   choose   the   leader   of   Pondok   Pesantren, headmaster, teacher and student of Madrasah Aliyah as the respondent  of  the  research.  The  technique  of  collecting  data used   in   this   research   was   observation,   interview   and documentation  and  it  analysed  throuh  reducing,  displaying and verifiying the data to get the conclusion qualitatively.   As the result of this research were mention in the following, first,  there  are  five  types  of  extracurricular  education  in founding   the   student   in   Madrasah   Aliyah   Mustafawiyah Purba  baru  Kabupaten  Mandailing Natal,  which  are  religion and  sport  program,  art  and  skill  activity,  student’s organisation,   and   educative   tour;  second,  education extracurricular  process  in  Madrasah  Aliyah  Mustafawiyah Purba  Baru  Kabupaten  Mandailing  Natal  is  running  well,  it seems  the activity  has  programmed  well,  time  and  place  is schedule regularly and selective, the method use is variative and  orientiate  to  the  the  doundation  of  the  student’s  moral, and the regularly evaluation; third, extracurricular education gives  posititive  impact  to  the  student’s  moral,  not  only  in relation  to  Allah  SWT  but  also,  to  teacher,  parents,  friends and  themself;  fourth,  the  inhibitor  factors  are:  the  lack  offacility,  unprofessional  teacher  with  low  religion  skill,  and the  low  quality  of  students  and;  fifth,  the  solution  is  the cooperation   of   the   foundation,   workshop,   reschedule effectively,  have  an  experienced  trainner,  giving  advices  and giving the punishment to students.